Language Feasibility in Students' Textbooks Grade 1 Elementary School - Budiono, Nugroho Bagus (Nur Science Institute, 2024)
Background: This study evaluates the language feasibility of the Grade 1 student textbook on the theme Kegemaranku (My Favorites) from the 2013 Curriculum published by the Ministry of Education and Culture, focusing on its conformity to students' developmental levels, communicative effectiveness, and the coherence of its content structure. Method: A qualitative descriptive approach with content analysis was employed. The data were collected from the Kegemaranku textbook and analyzed through an interactive model consisting of data reduction, data display, and conclusion drawing, based on the BSNP (National Education Standards Agency) textbook assessment guidelines. Results: The analysis revealed that the textbook achieved high feasibility scores: 94.79% for conformity with student development, 92.70% for communicativeness, and 96.35% for the alignment and integration of thought flow. These results categorize the textbook as